Implementation of Leadership Ethics and Transformational Leadership in Employee Performance - Fitria Marisya; Veny Mayasari; Sri Dweni Astuti; M Bambang Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The performance of employees and an organization's capacity to adjust to changes in the external environment are significantly influenced by leadership. This study aims to investigate the impact of transformational ethics and leadership on employee work practices. This study makes use of literature review or literature study techniques. It is envisaged that research using this qualitative methodology will offer profound insight into the Ethics and Transformational of a leader on the performance of staff. It was found that the influence of ethics on employee performance had significant results related to leadership ethics and transformational leadership on employee performance to improve the ability of employees to be ethical and the courage of employees because they get motivation from their leaders.